Study of Social Justice Theology in the Bible for God's People - Waruwu, Sabarani; Rogate Artaida Tiarasi Gultom; Dapot Damanik (Tinta Emas Institute, 2025)
The study of social justice theology in the Bible highlights the importance of the principle of justice as an integral part of religious teachings and the lives of God's people. This article examines the concept of justice in the context of the Old and New Testaments, highlighting the role of God, the prophets, and the teachings of Jesus Christ in upholding justice for the weak and oppressed. In addition, the article emphasizes the importance of social ocia and social justice, as well as the involvement of the church and the people in fighting for justice through real actions, such as social service, education, and advocacy. It is also emphasized that justice and love must go hand in hand, becoming the foundation for building a harmonious, inclusive, and just society. Through a theological and practical approach, this article invites God's people to become agents of change who actively fight for social justice in order to create a better and more peaceful world.